2020
DOI: 10.1186/s12935-020-01493-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Circ_002117 binds to microRNA-370 and promotes endoplasmic reticulum stress-induced apoptosis in gastric cancer

Abstract: Background Mounting evidence implicates circular RNAs (circRNAs) in various biological processes during cancer progression. Gastric cancer is a main cause of cancer-related deaths worldwide. Herein, we aimed at investigating whether circ_002117 mediates gastric cancer progression through endoplasmic reticulum (ER) stress. Methods Bioinformatics analysis detected differentially expressed circRNAs and their target miRNA candidates, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…For example, the overexpression of miR-328-3p, targeting ER metalloprotease 1 (ERMP1), prevented liver cancer cell proliferation and invasion in female nude mice by reducing phosphorylation [92]. RT-qPCR analyses of biopsy specimens and cell lines verified that miR-370 is upregulated in gastric cancer, and Circ_002117 inhibits miR-370 to stimulate ER stress-induced apoptosis [93]. Moreover, ER stress-induced exosomal miRNAs also contribute to the pathogenesis of cancer.…”
Section: Endoplasmic Reticulummentioning
confidence: 99%
“…For example, the overexpression of miR-328-3p, targeting ER metalloprotease 1 (ERMP1), prevented liver cancer cell proliferation and invasion in female nude mice by reducing phosphorylation [92]. RT-qPCR analyses of biopsy specimens and cell lines verified that miR-370 is upregulated in gastric cancer, and Circ_002117 inhibits miR-370 to stimulate ER stress-induced apoptosis [93]. Moreover, ER stress-induced exosomal miRNAs also contribute to the pathogenesis of cancer.…”
Section: Endoplasmic Reticulummentioning
confidence: 99%
“…Augmented circ_002117 expression induced ER stress by upregulating the UPR pathway components GRP78, IRE1, eIF2α, and CHOP, subsequently resulting in apoptosis in gastric cancer cells. The underlying mechanism involves circ_002117 forming a sponge with miR-370, upregulating the HERPUD1 level, and facilitating ER stress-induced apoptosis [ 148 ]. CircCDR1as is highly expressed in OSCCs.…”
Section: Ncrnas Regulate Upr In Cancer Progressionmentioning
confidence: 99%
“…We identified that the induction in caspase-3 and PARP-1 activation via TPD52L2 silencing might be a reason for the apoptotic-induced antitumor effect in gastric carcinoma cells (OXA resistant). It has been indicated that stimulation of ER stress can increase the apoptotic process and reduce the proliferation of gastric carcinoma cells [29]. In the existing study, we found the elevated expression level of PERK, GRP78, CHOP, and IRE1α in TPD52L2 knockdown OXA-resistant gastric carcinoma cells, as compared with the control siRNAtransfected cells.…”
Section: Discussionmentioning
confidence: 67%
“…It has been indicated that stimulation of ER stress can increase the apoptotic process and reduce the proliferation of gastric carcinoma cells [ 29 ]. In the existing study, we found the elevated expression level of PERK, GRP78, CHOP, and IRE1 α in TPD52L2 knockdown OXA-resistant gastric carcinoma cells, as compared with the control siRNA-transfected cells.…”
Section: Discussionmentioning
confidence: 99%